Etnomedisin Tumbuhan Obat untuk Mengobati Penyakit Hipertensi oleh Pengobat Tradisional di Kecamatan Ambalau Kabupaten Buru Selatan - Loilatu, Muhammad Fitrah; Ukratalo, Abdul M; Manery, Dodikrisno E; Pangemanan, Victory O (Jurnal Sains, Teknologi dan Kesehatan, 2024)
Hypertension is a condition in which blood pressure rises abnormally and continuously during several blood pressure checks. Traditional medicine is still used by the people of Indonesia in the current era of globalization, even though modern medicine has been applied. The purpose of this study was to study ethnomedicine medicinal plants for treating hypertension by traditional healers in Ambalau District, South Buru Regency. This type of research is descriptive qualitative with an observational exploratory design. Data was collected using in-depth interview techniques with 35 informants. Obtained data were analyzed qualitatively. The results showed that the types of plants used in the treatment of hypertension include: fragrant pandan, African leaves, lima leaves, order, soursop and soursop. This indicates that the healers in the Ambalau sub-district have the same knowledge in utilizing medicinal plants to treat hypertension. Apart from that, there are also similarities in the parts that are widely used, namely herbs and leaves.